Mapping Global Trends and Scholarly Networks in Multicultural Education Curriculum: A Bibliometric Study - Jobeda Khanom; Muthoifin; Andri Nirwana AN; Salma Nasrin (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to analyze global trends, collaboration, and scientific contributions in the multicultural education curriculum during 2000–2024. Theoretical framework: This research is based on the concept of multicultural and inclusive education and uses a bibliometric approach to map the development and structure of research. Literature review: The literature review comes from Scopus publications that discuss multicultural education, curriculum, and inclusivity, which shows an increasing concern for diversity in education. Methods: The method used was a bibliometric analysis of 532 Scopus publications, with analysis of keywords, authors, institutions, publication trends, and state contributions. Results: The results show an increase in publications by 13.05% per year. Collaboration is quite high, but international cooperation is still limited. The United States is a major contributor, with key themes such as cultural competence, diversity, and intercultural education. Implications: This research is useful for curriculum developers and policymakers to strengthen inclusive and diversity-based education, including in the context of Islamic education. Novelty: The novelty of this research lies in a comprehensive bibliometric analysis in mapping global trends, themes, and collaborations in multicultural education.